2023
DOI: 10.1038/s41586-023-06477-8
|View full text |Cite
|
Sign up to set email alerts
|

Central role of Tim17 in mitochondrial presequence protein translocation

Laura F. Fielden,
Jakob D. Busch,
Sandra G. Merkt
et al.

Abstract: The presequence translocase of the mitochondrial inner membrane (TIM23) represents the major route for the import of nuclear-encoded proteins into mitochondria1,2. About 60% of more than 1,000 different mitochondrial proteins are synthesized with amino-terminal targeting signals, termed presequences, which form positively charged amphiphilic α-helices3,4. TIM23 sorts the presequence proteins into the inner membrane or matrix. Various views, including regulatory and coupling functions, have been reported on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…By contrast, when a hydrophobic stop-transfer sequence is detected on the substrate, translocation stalls, the complex recruits subunits of the TIM23 SORT complex, and the nonpolar segment partitions laterally into the MIM as an α-helical transmembrane segment in a manner driven by the Δψ m (Gartner et al, 1995;Gruhler et al, 1997) and mediated by the ROMO1 and Tim21 gatekeepers (van der Laan et al, 2006;Mick et al, 2012;Ieva et al, 2014;Richter-Dennerlein et al, 2016;Richter et al, 2019;Lee et al, 2020). Notably, an alternative structure-based model of TIM23 function suggests that instead of forming an aqueous channel, Tim23 and Tim17 together form lipid-exposed cavities that provide a protein translocation pathway (Sim et al, 2023), consistent with evidence that TIM23 precursors are translocated across the MIM at the Tim17-bilayer interface rather than via a channel defined by Tim23 (Fielden et al, 2023).…”
Section: Structure and Function Of The Tim23 Complexmentioning
confidence: 55%
“…By contrast, when a hydrophobic stop-transfer sequence is detected on the substrate, translocation stalls, the complex recruits subunits of the TIM23 SORT complex, and the nonpolar segment partitions laterally into the MIM as an α-helical transmembrane segment in a manner driven by the Δψ m (Gartner et al, 1995;Gruhler et al, 1997) and mediated by the ROMO1 and Tim21 gatekeepers (van der Laan et al, 2006;Mick et al, 2012;Ieva et al, 2014;Richter-Dennerlein et al, 2016;Richter et al, 2019;Lee et al, 2020). Notably, an alternative structure-based model of TIM23 function suggests that instead of forming an aqueous channel, Tim23 and Tim17 together form lipid-exposed cavities that provide a protein translocation pathway (Sim et al, 2023), consistent with evidence that TIM23 precursors are translocated across the MIM at the Tim17-bilayer interface rather than via a channel defined by Tim23 (Fielden et al, 2023).…”
Section: Structure and Function Of The Tim23 Complexmentioning
confidence: 55%
“…The TIM23 machinery threads proteins through the inner membrane, assisted by the membrane potential (∆Ψ) and the presequence-associated motor (PAM) complex [72,73]. However, Tim17 and Tim23 facilitate local membrane thinning for protein translocation in contrast to Tom40 [74,75]. After successful translocation the mitochondrial processing peptidase (MPP) cleaves the MTS and the precursor is folded and or assembled [73].…”
Section: Mitochondrial Protein Importmentioning
confidence: 99%
“…The mechanistic and structural aspects of the different import routes have been studied extensively [8,73,75,83]. Nevertheless, the early steps of mitochondrial protein sorting and routing are in the process of being unraveled [99,100].…”
Section: Aimmentioning
confidence: 99%
“…Association of Tim21 (TIMM21 in mammals) and Mgr2 (ROMO1 in mammals) promotes the lateral translocation of proteins into the MIM, while association of the presequence translocase-associated motor (PAM) complex with the TIM23 core promotes the import of matrix proteins (8)(9)(10). Recent structural analysis showed that Tim17 forms the protein translocation path, whereas the associated Tim23 protein likely plays a structural role, serving as a platform that mediates the association of other complex subunits (11,12). Tim50, first discovered in yeast some two decades ago (13,14), is thought to be the first TIM23 complex component to interact with presequences of precursor proteins as they emerge from the Tom40 channel, thus playing a pivotal role in presequence-containing protein sorting (15).…”
Section: Introductionmentioning
confidence: 99%